Descriptive study of Caesarean sections in the Maternal and Child Hospital Canto Grande - Cam Pimentel, Gerardo (2015)
OBJETIVE: To determine the rate of cesarean section and main indications. PLACE: Maternity Hospital. Children Canto Grande of primary care. DESIGN: A descriptive, retrospective and cross-sectional study. MATERIALS AND METHODS: 429 pregnant you cesarean was studied. RESULTS: In 2003, there were 4072 births, 429 were by Caesarean section, giving a rate of 10.5%. In the age group 20 to 35 years 60% of the total and adolescents under 20 years 29.8% was performed. Common law marriage was 82.5% and only 6.7% were married. The main indications of cesarean section were: previous cesarean section (15.4%), breech presentation (13.5%), narrow pelvis (12.6% fetal macrosomia (11.9%) and acute fetal distress (10.5% .). CONCLUSIONS: The rate of cesarean section is the one that corresponds to a first level hospital where no obstetric surgery is practiced in high risk pregnancies, which are referred to hospitals in higher level Regarding the indications, differ very little in the other hospitals.